Principal Leadership Management In Teaching Learning Process Innovation - Iro Waziroh; M Tubi Heryandi; Muzammil Muzammil (Edukais : Jurnal Pemikiran Keislaman, 2022)
The leadership management of junior high school principals is one of the most important components of education to influence teachers, students, and teaching staff to innovate effective and efficient teaching and learning processes. On that basis, it is focused on the management profile of the principal's leadership in the innovation of the teaching and learning process with several supporting factors and the steps that are optimally implemented in the institution. This study used a qualitative approach with interview techniques, participatory observation, and documentation which took place at SMP Manbaul Ulum Tangsil Wetan Wonosari Bondowoso. Research findings are as follows: first, the management of the principal at SMP Manbaul Ulum has succeeded in innovating the teaching and learning process in its leadership by implementing good communication between leaders and teachers, Having competent teachers and staff, having a high commitment, Having good working mechanisms , able to make students have motivation and enthusiasm for learning by giving appreciation to students, The existence of adequate learning facilities and facilities. Second, the support of the school committee, parents and the surrounding community, a pleasant school environment. The division of tasks according to the field of teaching experts, Involving Subject Teacher Consultations (MGMP), training in the preparation of teaching and relevant equipment, training on curriculum implementation. The third finding is that the principal's leadership management has 4 main functions, namely; planning, implementation, supervision, and guidance. The steps taken are Curriculum Innovation, Student Innovation, Innovation for Human Resources Improvement, Learning Strategy Innovation, Infrastructure Innovation, Public Relations Innovation.